Ci-Symmetry, [2 × 2] grid, square copper complex with the N4, N5-bis(4-fluorophenyl)-1H-imidazole-4, 5-dicarboxamide ligand: structure, catecholase activity, magnetic properties and DFT calculations. (15th September 2017) - Parween, Arfa; Naskar, Sumita; Mota, Antonio J.; Espinosa Ferao, Arturo; Chattopadhyay, Shyamal Kumar; Rivière, Eric; Lewis, William; Naskar, Subhendu
Abstract : An antiferromagnetically coupled tetranuclear copper complex of a dinucleating bis amide ligand displays catecholase activity. Abstract : A new square tetranuclear copper complex of formulaCu4 (LH)4 ·4DMF with the dinucleating amide ligand N 4, N 5 -bis(4-fluorophenyl)-1 H -imidazole-4, 5-dicarboxamide (LH3 ) is reported herein. This ligand and the complex have been characterized by elemental analysis, FTIR, NMR, mass and UV-visible spectroscopy, as well as magnetic and electrochemical measurements. The single crystal X-ray diffraction study showed each Cu centre in a distorted square pyramidal environment, the square plane being formed by the extended coordination of two sets ( N, N and N, O ) of donor atoms from pairs of different ligands. The Cu4 unit has a C i symmetry and crystallises in the P 1̄ space group in between DMF layers. The electronic spectrum of the complex exhibits a d–d transition at 676 nm. The complex also displays mild catecholase activity in DMF solution by using 3, 5-di- tert -butylcatechol as substrate. Variable temperature magnetic measurements reveal an antiferromagnetic interaction between the copper centres with two different coupling constants of −143.4 and −169.0 cm −1 . DFT calculations made on a single Cu4 unit from the crystal structure corroborated the antiferromagnetic coupling, the spin density of the lower-energy broken-symmetry state being consistent with an alternating +−+− singlet state operating at low temperature.